2021
DOI: 10.3390/ijerph18168418
|View full text |Cite
|
Sign up to set email alerts
|

The Shinyanga Patient: A Patient’s Journey through HIV Treatment Cascade in Rural Tanzania

Abstract: The 2016–2017 Tanzania HIV Impact Survey (THIS) reported the accomplishments towards the 90-90-90 global HIV targets at 61-94-87, affirming the need to focus on the first 90 (i.e., getting 90% of people living with HIV (PLHIV) tested). We conducted a patient-pathway analysis to understand the gap observed, by assessing the alignment between where PLHIV seek healthcare and where HIV services are available in the Shinyanga region, Tanzania. We used existing and publicly available data from the National AIDS Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…They always adhere to the rule of confidentiality and their clients trust them with everything, rather than trusting health workers, who they fear might divulge their information as they are working in groups. Okere et al 6 and Rohwer et al 20 concur with the statement that resistance to attend health facilities for HIV treatment is due to the lack of confidentiality in the health facilities and the fear of unintentional disclosure of HIV status due to frequent clinic visits. Also sharing the same narrative are findings in the study 3 conducted in rural Uganda that clients easily confide in their traditional healers rather than in health institutions, as they are afraid of their HIV status being known.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…They always adhere to the rule of confidentiality and their clients trust them with everything, rather than trusting health workers, who they fear might divulge their information as they are working in groups. Okere et al 6 and Rohwer et al 20 concur with the statement that resistance to attend health facilities for HIV treatment is due to the lack of confidentiality in the health facilities and the fear of unintentional disclosure of HIV status due to frequent clinic visits. Also sharing the same narrative are findings in the study 3 conducted in rural Uganda that clients easily confide in their traditional healers rather than in health institutions, as they are afraid of their HIV status being known.…”
Section: Discussionmentioning
confidence: 91%
“…Both the Ministry of Health and traditional healers should work together to achieve proper management of HIV and AIDS by both health institutions and traditional healers, with neither misleading the other due to a lack of knowledge on the part of the traditional healers and their clients. The study 6 conducted in rural Tanzania found that denial amongst those infected with HIV is an issue and that there is a lack of knowledge when it comes to the management of HIV by traditional healers, as they believe that they can heal HIV.…”
Section: Introductionmentioning
confidence: 99%